2022
DOI: 10.3389/fpos.2022.920567
|View full text |Cite
|
Sign up to set email alerts
|

Puzzles in affective polarization research: Party attitudes, partisan social distance, and multiple party identification

Abstract: Affective polarization refers to people having favorable attitudes toward their preferred political parties, or inparties, along with their supporters, and negative attitudes toward other parties, or outparties, and their supporters. Originally an American concept, there is now growing interest in studying (AP) in European countries characterized by multiparty systems. So far, researchers have primarily focused on like-dislike ratings when measuring affect, which has relegated another important aspect to the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…All in all, the rise of party competition due to multiparty systems tends to promote social confrontation instead of confronting ideas as a way to obtain electoral credit. This differentiation strategy consists of indicating 'the bad ones' (out-partisans) in contrast to 'the good ones' (partisans) (Kekkonen et al, 2022). This idea connects to the individual dimension of AP, in which political speech is regarded as a tool to fuel animosity among individuals.…”
Section: Identities and Parties: The Complexity Of A Multiparty Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…All in all, the rise of party competition due to multiparty systems tends to promote social confrontation instead of confronting ideas as a way to obtain electoral credit. This differentiation strategy consists of indicating 'the bad ones' (out-partisans) in contrast to 'the good ones' (partisans) (Kekkonen et al, 2022). This idea connects to the individual dimension of AP, in which political speech is regarded as a tool to fuel animosity among individuals.…”
Section: Identities and Parties: The Complexity Of A Multiparty Systemmentioning
confidence: 99%
“…One of the main contributors to the task of understanding AP from a multiparty approach is Wagner (2021), who indicates that, while measuring AP in a two-party system is relatively manageable, the act of assuming the challenge of measuring AP in a multiparty system is much complex due to the number of variables, actors, relationships, and effects that need to be considered. Consequently, there is a clear need for the provision of more theoretical and empirical work on the rise of AP in multiparty systems (Medeiros & Noël, 2014;Abramowitz & Webster, 2016;Mayer, 2017;Kekkonen & Ylä-Anttila, 2021;Kekkonen et al, 2022). In this respect, one aspect that notably changes when moving from a two-party system to a multiparty system is that of partisan ties and the relationship with political outgroups.…”
Section: Identities and Parties: The Complexity Of A Multiparty Systemmentioning
confidence: 99%
“…While in the USA two-party system, researchers can simply look at the gap between the in-party and the out-party to assess affective polarization, applying the concept to multi-party systems such as those predominant in Europe poses immediate challenges. First, positive party identification is generally in decline in Europe (Heath, 2017), while multiple party identification is possible (e.g., Kekkonen et al, 2022). Complex party systems mean that Europeans are not faced with two partisan groups of roughly equal size, but with a sometimes dizzying array of unstable and ephemeral parties.…”
Section: Introductionmentioning
confidence: 99%
“…These allow respondents to state whether they would be happy or unhappy to have party supporters as their colleague, neighbour or relative (Helbling and Jungkunz, 2020;Knudsen, 2021;Gidron et al, 2022). Kekkonen et al (2022) showed that social distance is consistently lower than simple out-party dislike. Trait ratings are another popular measure, as used most notably in Hobolt et al (2021).…”
Section: Introductionmentioning
confidence: 99%
“…In terms of Nordic countries, recent studies have shown increases in affective polarization in Sweden and Finland during recent election years (Kawecki, 2022;Kekkonen & Ylä-Anttila, 2021;Oscarsson et al, 2021) and that people in Norway, Finland and Sweden display polarized feelings toward supporters of out-parties, that is, negative trait ratings and a willingness to distance oneself socially from out-party supporters (Kekkonen et al, 2022;Knudsen, 2021;Renström et al, 2020Renström et al, , 2022. However, since the research field is still at an early stage and based on single case studies, there are potentially valuable insights to be made from studies that bring together trends in affective polarization for the Nordic countries.…”
Section: Introductionmentioning
confidence: 99%